Henry Roseveare, Markets and Merchants of Late Seventeenth Century. The Marescoe- David Letters 1668-1680 - Ρενιέρη Ειρήνη (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1990)
[ Δε διατίθεται περίληψη / no abstract available]